Lost to desire the École Psychosomatique de Paris and its encounter with patients who do not thrive - Lassmann, Wolfgang (Routledge, Taylor & Francis Group, 2022)
"This book covers the work of psychoanalysts in post WWII France with patients beset by somatic problems with little manifest fantasy life, and how their concept of opératoire continues to inform the theory and practice of working with patients in crisis. The author explores what the new concept has elicited in a community of practitioners - close to the École Psychosomatique de Paris - over a period of some sixty years. As a "skin for thought" it facilitated change while preserving coherence, gradually beginning to attract further considerations. Important themes have included: the early groundwork necessary for the configuration of fantasy, the importance of a shared imaginary, the role of denial and obliterated memories as a bond between people, emergency measures of a Me cut off from revitalisation, the effects of the rhythms and atmosphere at the workplace on family life, and the consequences of a crisis suppressed for lack of a holding frame. As psychoanalytic discourse adapted to the challenges, the original perspective changed aspect, moving from a systematic evaluation of what the patients did not produce to what the analyst had to fill in to make sense of the situation. Clashing with the terrain, French psychoanalysts raised important problems about psychic anaemia that are stimulating and deserve cross-cultural discussion. This book will appeal to psychoanalysts in practice and training who wish to learn more about this ground-breaking work on memory and trauma, and how to apply it to their own practice"--
Keywords: Geschichte 1940-2000; Psychoanalyse; Frankreich; Psychoanalysis / France / History / 20th century; Memory; Psychic trauma; Psychoanalysis; France; 1900-1999; History